AIR DRONES GROUP CAPACITY ESTIMATION DURING MONITORING MISSION - Dmytro P. Kucherov; Andrii M. Kozub (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
In this paper is considered the calculation of capacity information which comes from an unmanned aircraft vehicles group (UAVs) performing the task of monitoring the ground environment. It is assumed that a group of UAVs can perform the task of monitoring in concert with centralized control or completely different tasks each member of the group. Both versions with UAVs must used from one control point. The capacity of received packets of information is increases. Principle of processing information packets in one presupposes a buffer store, where the information is built in the queue. For the main results are used essentially theoretical approaches used for analysis of information systems with queues. To analyze the capacity of selected indicators of absolute and relative bandwidth server data processing and bit volume of buffer storage. The main assumption, which proposed for typical calculating bandwidth assumes an exponential distribution input data by Poisson law. In real situations, data processing takes some time, which leads to aftereffect. Therefore, to solve this problem and proposed to carry out accounting aftereffect in the flow of services. A special feature is the calculation of accounting aftereffect in the information that it was possible, if we abandon the exponential distribution of intervals between events, and to replace it with a second-order flow Erlang. Adequacy of calculations confirmed estimates that given by the formulas Poliaček-Khinchin. The article provides a numerical example of the calculation based on both approaches.